THE ROLE OF MEZZANINE CAPITAL IN FINANCING ENTREPRENEURIAL ACTIVITY AND ITS LEGAL REGULATION (TSUL LEGAL REPORT, 2026)
This article aims to examine the role of mezzanine financing – a non-traditional, hybrid instrument – in situations where conventional methods (bank loans, leasing) lack flexibility and sufficient risk appetite for innovative projects. Mezzanine finance combines elements of debt and equity, allowing companies to attract substantial capital without diluting existing shareholding, and holds an intermediate position in the priority ranking during insolvency, situated between senior creditors and shareholders. The core of the research consists of a comparative analysis of mezzanine’s legal regulation. The article details the relationships between the key participants in a Mezzanine transaction – the borrower, the senior creditor, and the mezzanine creditor – including their priority, the collateral (shares/equity interests), and return requirements. The conclusion substantiates the need to implement relevant norms into Uzbekistan’s national legislation, drawing on the similarities between mezzanine and existing financing types, including the introduction of accelerated foreclosure procedures and the establishment of legal certainty for private investments.